Positive pole piece, preparation method, lithium ion battery and electric device

By adopting a positive pole sheet composed of active materials such as lithium iron phosphate and lithium nickel cobalthogite, lithium ion batteries that are difficult to meet the problems of high energy density and high power density density, the battery has been solved. The stable performance under low temperature conditions has extended the battery life and reduced the management difficulty of the battery management system.

CN119381398APending Publication Date: 2025-01-28NIO BATTERY TECH (ANHUI) CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202310928309.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-25
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Existing lithium-ion batteries are difficult to meet the needs of high energy density and high power density at the same time, and perform poorly under high and low temperature conditions, resulting in increased management difficulties of battery management systems and shortened battery life.

Method used

Adopt a positive pole film composed of a positive album, the first material layer, and the second material layer. The first material layer contains active materials such as lithium iron phosphate and lithium nickel cobaltate. Active materials, through optimized material composition and hierarchical structure, improve the energy density and power density of the battery.

Benefits of technology

The discharge interval of the lithium ion battery is extended, the battery discharge capacity under low SOC is improved, the end voltage difference between different battery discharge end voltage is reduced, the individual battery is used for discharge, the life of the battery pack is extended, and the battery management system is reduced. Management difficulty.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381398A_ABST
    Figure CN119381398A_ABST
Patent Text Reader

Abstract

The invention provides a positive pole piece. The positive pole piece comprises a positive current collector, a first material layer arranged on at least one surface of the positive current collector, and a second material layer arranged on the surface, far away from the positive current collector, of the first material layer, the first material layer comprises an active material A and an active material B; the second material layer comprises an active material C; the active material A is selected from lithium iron phosphate and / or lithium manganese iron phosphate; the active material B is selected from one or more of nickel cobalt lithium manganate, lithium cobalt oxide, lithium manganate and nickel lithium manganate; the active material C is selected from one or more of nickel cobalt lithium manganate, lithium cobalt oxide, lithium manganate and nickel lithium manganate; by using the positive pole piece provided by the invention, the interface impedance of the pole piece can be reduced, the problem that the expansion rates of different areas of the pole piece are different is solved, and the cycle life of the battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of lithium battery materials, and in particular to a positive electrode sheet for a lithium battery, a method for preparing the positive electrode sheet, a lithium ion battery including the positive electrode sheet, and an electrical device. Background Art

[0002] With the rapid development of electric vehicles, the requirements for lithium-ion batteries are getting higher and higher. Lithium-ion batteries not only need to have high energy density and high power density, but also need to have excellent high temperature performance, long cycle life and high safety. However, at this stage, the energy density of commercial lithium-ion batteries is low, and it is difficult to meet both high energy density and high power density at the same time, which cannot meet the growing demand for electric vehicles. Therefore, the development of high energy density and high power density lithium-ion batteries has become a hot topic in today's social research and a trend in industry development, which plays an important role in promoting the development of electric vehicles.

[0003] According to the development plan of power battery technology, the energy density of single cells needs to reach 400Wh / Kg in 2025. Combined with the performance comparison of existing batteries at all levels, it can be seen that there is still a lot of room for improvement in the energy density of batteries at the material level and electrode level. As the source and carrier of battery energy, the positive electrode material of lithium-ion batteries is of great help in improving the energy density of lithium-ion batteries. Among them, the lower limit of the voltage of ternary lithium batteries, that is, lithium batteries using ternary positive electrode materials of nickel cobalt manganese oxide (Li(NiCoMn)O2) or nickel cobalt aluminum oxide, is generally 2.8V. Since its capacity is mainly concentrated above 3.3V, the slope at the end of the discharge curve is very steep, resulting in poor consistency of each cell at the end of the battery pack discharge, which increases the difficulty of active balancing management of BMS (battery management system); in order to avoid the risk of over-discharge caused by individual batteries with shortcomings, the voltage usage range can only be further compressed, so that the actual mileage is further reduced compared to the nominal mileage. In addition, how to reduce the interface impedance of lithium-ion batteries at low temperatures is also one of the problems in the industry. Summary of the invention

[0004] In view of the problems existing in the prior art, the present disclosure provides a positive electrode sheet, the positive electrode sheet comprising a positive electrode current collector, a first material layer disposed on at least one surface of the positive electrode current collector, and a second material layer disposed on a surface of the first material layer away from the positive electrode current collector; the first material layer comprises active material A and active material B; the second material layer comprises active material C; wherein:

[0005] The active material A is selected from lithium iron phosphate and / or lithium iron manganese phosphate;

[0006] The active material B is selected from one or more of lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium manganese oxide and lithium nickel manganese oxide;

[0007] The active material C is selected from one or more of lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium manganese oxide and lithium nickel manganese oxide.

[0008] In one aspect of the present disclosure, the first material layer has a thickness of 15-40 μm.

[0009] In one aspect of the present disclosure, the second material layer has a thickness of 60-135 μm.

[0010] In one aspect of the present disclosure, in the first material layer, a mass ratio of the active material A to the active material B is 1:3 to 3:1.

[0011] In one aspect of the present disclosure, based on the total weight of the active material A, the active material B and the active material C, the weight percentage of the active material A is 2.5% to 30.0%.

[0012] In one aspect of the present disclosure, based on the total weight of the active material A, the active material B and the active material C, the weight percentage of the active material A is 2.5% to 6.2%.

[0013] The present disclosure also provides a method for preparing the aforementioned positive electrode sheet, the method comprising the following steps:

[0014] Step 1: Active material A, active material B, a binder and a conductive agent are stirred evenly by dry mixing, and then N-methylpyrrolidone is added and stirred evenly to obtain a first positive electrode slurry;

[0015] Step 2: coating the first positive electrode slurry onto at least one surface of the positive electrode current collector, wherein the single-side coating thickness is 15-40 μm, and drying to obtain a pole piece including the first material layer;

[0016] Step 3: stir the active material C, the binder and the conductive agent evenly by dry mixing, and then add N-methylpyrrolidone and stir evenly to obtain a second positive electrode slurry;

[0017] Step 4: coating the second positive electrode slurry onto the surface of the electrode sheet obtained in step 2 away from the positive electrode current collector, wherein the single-side coating thickness is 60-135 μm, and drying to obtain the positive electrode sheet.

[0018] In one aspect of the present disclosure, the solid content of the first positive electrode slurry and the second positive electrode slurry is 45% to 78%, and the viscosity is 3000 mPa·s to 15000 mPa·s.

[0019] In one aspect of the present disclosure, in the first material layer, the mass ratio of the active material A to the active material B is (1:3) to (3:1); preferably (0.75:1) to (1:0.75), and more preferably 1:1.

[0020] In one aspect of the present disclosure, based on the total weight of the active material A, the active material B and the active material C, the weight percentage of the active material A is 2.5% to 30.0%; the weight percentage of the active material B is 2.5% to 30.0%; and the weight percentage of the active material C is 60% to 90%.

[0021] In one aspect of the present disclosure, in the first material layer, the maximum particle size of the active material A and the active material B is less than or equal to 15 μm.

[0022] In one aspect of the present disclosure, in the first material layer, the average particle size of the active material A is 0.4-2.0 μm, preferably 0.7-1.4 μm.

[0023] In one aspect of the present disclosure, in the first material layer, the average particle size of the active material B is 2.5-20.0 μm, preferably 2.8-14.0 μm.

[0024] In one aspect of the present disclosure, in the second material layer, the maximum particle size of the active material C is less than or equal to 43.0 μm.

[0025] In one aspect of the present disclosure, in the second material layer, the average particle size of the active material C is 2.5-20.0 μm, preferably 2.8-14.0 μm.

[0026] In one aspect of the present disclosure, in the first material layer, the maximum particle size of the active material A and the active material B is less than or equal to 15 μm.

[0027] In one aspect of the present disclosure, the ratio of the average particle size of active material B to the average particle size of active material A is selected from 3:1 to 13:1.

[0028] In one aspect of the present disclosure, preferably, the ratio of the average particle size of active material B to the average particle size of active material A is selected from 3:1 to 5:1.

[0029] In one aspect of the present disclosure, the ratio of the average particle size of active material C to the average particle size of active material A is selected from 3:1 to 13:1.

[0030] In one aspect of the present disclosure, preferably, the ratio of the average particle size of the active material C to the average particle size of the active material A is selected from 3:1 to 5:1.

[0031] In one aspect of the present disclosure, the positive electrode current collector is selected from ordinary aluminum foil, porous aluminum foil and carbon-coated aluminum foil, but is not limited thereto.

[0032] In one aspect of the present disclosure, the solid content of the first positive electrode slurry and the second positive electrode slurry is 57% to 72%, and the viscosity is 6000 mPa·s to 12000 mPa·s.

[0033] In one aspect of the present disclosure, in the first positive electrode slurry, based on the weight of the first positive electrode slurry, the sum of the mass percentages of active material A and active material B is 96.0% to 97.5%, the mass percentage of the binder is 0.8% to 2.5%, and the mass percentage of the conductive agent is 0.5% to 2.0%.

[0034] In one aspect of the present disclosure, in the second positive electrode slurry, based on the weight of the second positive electrode slurry, the mass percentage of active material C is 96.0% to 97.5%, the mass percentage of binder is 0.8% to 2.5%, and the mass percentage of conductive agent is 0.5% to 2.0%.

[0035] In one aspect of the present disclosure, in step 2 and step 4 of the preparation process, the drying temperature is 110°C to 150°C.

[0036] The present disclosure also provides a lithium-ion battery, which includes the aforementioned positive electrode plate, and further includes a negative electrode plate and an electrolyte.

[0037] The present disclosure also provides an electrical device, which includes the aforementioned lithium-ion battery.

[0038] Beneficial effects:

[0039] Generally, the charge and discharge range of general ternary cathode materials is 2.5V to 4.2V, but general ternary cathode materials have a steep discharge curve when discharging (see Figure 1 As shown in the curve of the discharge voltage variation over time of Comparative Example 1 in the figure, since the attenuation consistency of each battery cell is not exactly the same, the voltages at the discharge ends of different battery cells are inconsistent. If one of the battery cells is triggered to be cut off, the entire battery management system will be cut off. By using the positive electrode plate provided by the present disclosure, since the discharge platform of lithium iron phosphate or lithium iron manganese phosphate is around 3.2V, the positive electrode material will be delayed at around 3.2V during discharge, that is, it will have a relaxation effect, so that the discharge voltage will be as follows: Figure 1The gentle slope shown in Example 1 and the extended discharge interval not only improve the discharge capacity of the single cell at low SOC, but also reduce the voltage difference at the discharge end of different cells, effectively preventing over-discharge of individual cells, thereby increasing the life of the battery pack and reducing the management difficulty of the battery management system. In addition, the positive electrode plate provided by the present disclosure also avoids the problem of reduced battery energy density caused by excessive content of lithium iron phosphate and / or lithium iron manganese phosphate.

[0040] In addition, part of the lithium iron phosphate and / or lithium iron manganese phosphate exists near the current collector side, and the carbon coating layer on its surface can reduce the interface impedance, reduce the overall impedance, and improve the performance at low temperatures. At the same time, it avoids the problem that the lithium at the interface cannot be embedded and removed in time during high-rate charging and discharging, causing the failure of the active lithium and the deterioration of performance. In addition, the material blending method is selected in the first active layer to avoid the different expansion caused by the inconsistency of the upper and lower materials during the cycle, and avoids the accumulation of stress that may cause the contact between the two active layers to deteriorate, which affects the long-term cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 A graph showing the discharge voltage versus time for an example is shown. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical solution and advantages of the present disclosure clearer, the technical solution of the present disclosure will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present disclosure, rather than all the embodiments. The relevant embodiments described herein are illustrative and are used to provide a basic understanding of the present disclosure. The embodiments of the present disclosure should not be interpreted as limiting the present disclosure.

[0043] the term:

[0044] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.

[0045] In this article, the terms "comprises", "comprising" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device that includes a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of more restrictions, an element defined by the sentence "comprising a ..." does not exclude the presence of other identical elements in the process, method, article or device that includes the element.

[0046] In this document, it is necessary to understand that the orientations or positional relationships indicated by the terms "upper", "lower", "top", "bottom", "inside", "outside", etc. are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present disclosure and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present disclosure.

[0047] In the description herein, unless otherwise specified, “above” and “below” include the number.

[0048] Unless otherwise specified, the terms used in this disclosure have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values ​​of the various parameters mentioned in this disclosure can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this disclosure).

[0049] The term "about" is used to describe and illustrate small changes. When used in conjunction with an event or situation, the term may refer to an example in which the event or situation occurs precisely and an example in which the event or situation occurs very approximately. For example, when used in conjunction with a numerical value, the term may refer to a range of variation of less than or equal to ±10% of the numerical value, such as less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%. In addition, amounts, ratios, and other numerical values ​​are sometimes presented in this article in a range format. It should be understood that such a range format is for convenience and simplicity, and should be flexibly understood to include not only numerical values ​​explicitly designated as range limits, but also all individual numerical values ​​or subranges encompassed within the range, as if each numerical value and subrange were explicitly designated.

[0050] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.

[0051] The thickness of the active layer mentioned in the present invention refers to the thickness of the active material coated on one side of the electrode.

[0052] The present disclosure is further described below in conjunction with specific embodiments. It should be understood that these specific embodiments are only used to illustrate the present disclosure and are not used to limit the scope of the present disclosure.

[0053] positive electrode:

[0054] In some embodiments of the present disclosure, the lithium-ion battery provided by the present disclosure includes a positive electrode, which uses the positive electrode plate provided by the present disclosure, and the positive electrode plate includes a positive electrode collector, a first material layer arranged on at least one surface of the positive electrode collector, and a second material layer arranged on the surface of the first material layer away from the positive electrode collector; the first material layer contains active material A and active material B; the second material layer includes active material C; wherein: the active material A is selected from lithium iron phosphate and / or lithium manganese iron phosphate; the active material B is selected from one or more of lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium manganese oxide and lithium nickel manganese oxide; the active material C is selected from one or more of lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium manganese oxide and lithium nickel manganese oxide.

[0055] In some embodiments of the present disclosure, the first material layer has a thickness of 15-40 μm.

[0056] In some embodiments of the present disclosure, the second material layer has a thickness of 60-135 μm.

[0057] In some embodiments of the present disclosure, in the first material layer, a mass ratio of the active material A to the active material B is 1:3 to 3:1.

[0058] In some embodiments of the present disclosure, based on the total weight of the active material A, the active material B and the active material C, the weight percentage of the active material A is 2.5% to 30.0%.

[0059] In some embodiments of the present disclosure, the first material layer and the second material layer further include a binder, and optionally also include a conductive material. The binder improves the bonding between the positive electrode active material particles and also improves the bonding between the positive electrode active material and the current collector.

[0060] In some embodiments of the present disclosure, non-limiting examples of binders include polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, and the like.

[0061] In some embodiments of the present disclosure, the first material layer and the second material layer also include a conductive material to give the electrode conductivity. The conductive material may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.

[0062] negative electrode:

[0063] In some embodiments of the present disclosure, the lithium-ion battery provided by the present disclosure further includes a negative electrode, the negative electrode includes a negative electrode plate, the negative electrode plate includes a current collector and a negative electrode active material layer disposed on the current collector. The specific types of negative electrode active materials are not subject to specific restrictions and can be selected according to needs. Specifically, the negative electrode active material is selected from natural graphite, artificial graphite, mesophase microcarbon beads (abbreviated as MCMB), hard carbon, soft carbon, silicon, silicon-carbon composites, Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO 2 , spinel-structured lithiated TiO 2 -Li 4 Ti 5 O 12 , Li-Al alloy. Non-limiting examples of carbon materials include crystalline carbon, amorphous carbon and mixtures thereof. Crystalline carbon can be amorphous or flake-shaped, platelet-shaped, spherical or fibrous natural graphite or artificial graphite. Amorphous carbon can be soft carbon, hard carbon, mesophase pitch carbide, calcined coke, etc.

[0064] In some embodiments of the present disclosure, the negative electrode active material layer may include a binder and optionally a conductive material. The binder improves the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector.

[0065] In some embodiments of the present disclosure, non-limiting examples of binders include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, and the like.

[0066] In some embodiments of the present disclosure, the negative electrode active material layer includes a conductive material so that the electrode has conductivity. The conductive material may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., such as copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.

[0067] In some embodiments of the present disclosure, the negative electrode sheet of the present disclosure includes a negative electrode active material, a binder and a conductive agent.

[0068] In some embodiments of the present disclosure, the negative electrode active material of the present disclosure may also be selected from other materials that can electrochemically absorb and release metal ions such as lithium ions. Specifically, it can be selected from carbonaceous materials, silicon materials, alloy materials, lithium-containing metal oxide materials, etc. They can be used alone or in any combination of two or more.

[0069] In some embodiments of the present disclosure, the negative electrode current collector may be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.

[0070] Diaphragm:

[0071] In some embodiments of the present disclosure, the electrochemical device of the present disclosure is provided with a separator between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator used in the electrochemical device of the present disclosure are not particularly limited, and it can be any technology disclosed in the prior art.

[0072] In some embodiments of the present disclosure, the separator includes a polymer or an inorganic substance formed of a material that is stable to the electrolyte of the present disclosure.

[0073] In some embodiments of the present disclosure, the separator may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film with a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide.

[0074] Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used.

[0075] A surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.

[0076] The inorganic layer comprises inorganic particles and a binder, wherein the inorganic particles are selected from one or a combination of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate. The binder is selected from one or a combination of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinyl pyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.

[0077] The polymer layer contains polymers, and the material of the polymer is selected from at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride, and poly(vinylidene fluoride-hexafluoropropylene).

[0078] Electrolyte:

[0079] In some embodiments of the present disclosure, the lithium-ion battery and electrochemical device involved in the present disclosure further include an electrolyte.

[0080] In some embodiments, the electrolyte includes a lithium salt and a solvent.

[0081] In some embodiments, the lithium salt includes at least one of an organic lithium salt or an inorganic lithium salt. In some embodiments, the lithium salt includes, but is not limited to: lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium difluorophosphate (LiPO 2 F 2 ), bis(trifluoromethanesulfonyl)imide lithium LiN (CF 3 SO 2 ) 2 (LiTFSI), lithium bis(fluorosulfonyl)imide Li(N(SO 2 F) 2 )(LiFSI), LiB(C 2 O 4 ) 2 (LiBOB) or lithium difluorooxalatoborate LiBF 2 (C 2 O4 In some embodiments, the concentration of the lithium salt in the electrolyte is about 0.5 mol / L to 3 mol / L, about 0.5 mol / L to 2 mol / L, or about 0.8 mol / L to 1.5 mol / L.

[0082] In some embodiments, the solvent can be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0083] In some embodiments, the electrolyte may also optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, additives that improve battery low temperature performance, etc.

[0084] Lithium-ion battery:

[0085] In some embodiments of the present disclosure, the lithium-ion battery involved in the present disclosure includes the above-mentioned positive electrode plate, negative electrode plate, separator, electrolyte, etc., but is not limited thereto.

[0086] In some embodiments of the present disclosure, the lithium-ion battery involved in the present disclosure may include an outer packaging, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.

[0087] In some embodiments of the present disclosure, the present disclosure further provides a battery module. The battery module includes the above-mentioned lithium-ion battery. The battery module of the present disclosure uses the above-mentioned lithium-ion battery, and therefore has at least the same advantages as the lithium-ion battery. The number of lithium-ion batteries contained in the battery module of the present disclosure can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.

[0088] In some embodiments of the present disclosure, the present disclosure further provides a battery pack, which includes the above-mentioned battery module. The number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.

[0089] Electrical devices:

[0090] In some embodiments of the present disclosure, the electrical device includes, but is not limited to: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, power storage systems, etc. In order to meet the device's requirements for high power and high energy density of lithium-ion batteries, a battery pack or battery module may be used.

[0091] In other embodiments of the present disclosure, the power-consuming device may be a mobile phone, a tablet computer, a laptop computer, etc. The device is usually required to be light and thin, and a lithium-ion battery may be used as a power source.

[0092] The present disclosure is further described below in conjunction with the examples. It should be understood that these examples are only used to illustrate the present disclosure and are not used to limit the scope of the present disclosure.

[0093] Example:

[0094] Test method:

[0095] Capacity retention at -20°C:

[0096] The battery cell is placed at room temperature, fully charged at a 1 / 3C rate, and discharged to a cut-off voltage at a 1 / 3C rate. The capacity released is recorded as C0; the battery cell is placed at room temperature, fully charged at a 1 / 3C rate, placed in a constant temperature environment of -20°C for 12 hours, and then discharged to a cut-off voltage at a 0.6C rate. The capacity retention rate at -20°C is C1 / C0.

[0097] 3C rate capacity retention rate:

[0098] The battery cell is placed at room temperature, fully charged at a 1 / 3C rate, and discharged to a cut-off voltage at a 1 / 3C rate, and the capacity released is recorded as C0; the battery cell is placed at room temperature, fully charged at a 1 / 3C rate, and discharged to a cut-off voltage at a 3C rate, and the capacity released is recorded as C2; the 3C rate capacity retention rate is C2 / C0.

[0099] Impedance test:

[0100] The battery cell is adjusted to a charged state of 50% SOC by charging and discharging. The voltage after standing for 30 minutes is taken as U1. The current I 2 The voltage after 30s of discharge is recorded as U2, and the internal resistance DCR = (U2-U1) / I 2 .

[0101] Cycle life test:

[0102] In a constant temperature environment of 45°C, in the voltage range of 2.5V-4.2V, after charging to 3.8V with 2C constant current, then charging to 4.2V with 1C constant current and constant voltage, with a cutoff current of 0.05C and a cycle life test with 1C discharge. The test cutoff condition is that the capacity decays to 80% of the initial capacity.

[0103] Embodiment 1:

[0104] Embodiment 1 is divided into the following steps:

[0105] 1. Preparation of positive electrode sheet:

[0106] (1) Weigh the materials according to the following weight ratio: (active material: binder: conductive agent = 97.0:1.5:1.5), wherein the active material consists of active material A and active material B, active material A is selected from carbon-coated lithium iron phosphate, active material B is selected from nickel cobalt manganese oxide, and the weight ratio of active material A to active material B is 25:75. Put the above materials into a planetary vacuum disperser and dry mix them for 30 minutes; then add an organic solvent NMP with a weight of 30% of the total weight of the above materials, stir for 1 hour, and then add an appropriate amount of NMP and disperse at high speed for 3 hours to prepare a qualified slurry with a viscosity in the range of 4000mPa·s-9000mPa·s.

[0107] (2) The qualified positive electrode slurry is coated onto an aluminum foil current collector with a single-side coating thickness of 30 μm, and then dried in an oven to obtain a pole piece including a first material layer.

[0108] (3) Weigh the materials according to the following weight ratio: (active material C: binder: conductive agent = 97.0:1.5:1.5), wherein the active material C is selected from lithium nickel cobalt manganese oxide, and place the above materials in a planetary vacuum disperser for dry mixing for 30 minutes; then add an organic solvent NMP whose weight is 30% of the total weight of the above materials, stir for 1 hour, add an appropriate amount of NMP and disperse at high speed for 3 hours to prepare a qualified slurry with a viscosity falling within the range of 4000mPa·s-9000mPa·s.

[0109] (4) The positive electrode slurry obtained in (3) is applied to the electrode sheet prepared in (2) with a single-side coating thickness of 90 μm, and then dried in an oven to obtain a composite positive electrode sheet. In the obtained composite positive electrode sheet, the mass percentage of active material A is about 6.2% based on the total mass of active material A, active material B and active material C.

[0110] 2. Preparation of negative electrode sheet:

[0111] Artificial graphite, conductive agent Super P, thickener sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) are fully stirred and mixed in an appropriate amount of deionized water solvent according to a weight ratio of 95.0:1.5:1.5:2 to form a uniform negative electrode slurry. The slurry is coated on the negative electrode current collector copper foil, dried and cold pressed to obtain a negative electrode active material layer, and then cut, slit, and welded to the pole ear to obtain the negative electrode.

[0112] 3. Preparation of lithium-ion batteries:

[0113] The prepared positive electrode, negative electrode and separator (composed of a 9 μm PE polyethylene film coated with a 2 μm boehmite ceramic coating on both sides) were stacked in order, so that the separator was placed between the positive electrode and the negative electrode to play an isolating role, and then wound to obtain a bare cell; the bare cell was placed in an outer packaging foil aluminum-plastic film, and the electrolyte (50% EMC + 30% EC + 20% DEC + 1.1M LiPF6 +

[0114] 1%LiPO 2 F 2 +1% VC (vinyl carbonate) +1% FEC) is injected into the dried bare battery cell, and the preparation of the lithium-ion battery is completed through processes such as vacuum packaging, standing, formation, shaping, and capacity testing.

[0115] Embodiment 2:

[0116] The steps of Example 2 are the same as those of Example 1, except that, in the preparation process of the positive electrode sheet, in step (2), the thickness of the single-sided coating is changed from 30 μm to 15 μm; in step (4), the thickness of the single-sided coating is changed from 90 μm to 135 μm. In the composite positive electrode sheet obtained in Example 2, the mass percentage of active material A is 2.5% based on the total mass of active material A, active material B and active material C.

[0117] Embodiment 3:

[0118] The steps of Example 3 are the same as those of Example 1, except that, during the preparation of the positive electrode sheet, the weight ratio of active material A to active material B is adjusted from 25:75 to 40:60; based on the total mass of active material A, active material B and active material C, the mass percentage of active material A is 10.0%.

[0119] Embodiment 4:

[0120] The steps of Example 4 are the same as those of Example 1, except that, during the preparation of the positive electrode sheet, the weight ratio of active material A to active material B is adjusted from 25:75 to 50:50; based on the total mass of active material A, active material B and active material C, the mass percentage of active material A is 12.5%.

[0121] Embodiment 5:

[0122] The steps of Example 5 are the same as those of Example 1, except that, during the preparation of the positive electrode sheet, the weight ratio of active material A to active material B is adjusted from 25:75 to 60:40, and in step (2), the thickness of the single-sided coating is changed from 30 μm to 40 μm; in step (4), the thickness of the single-sided coating is changed from 90 μm to 80 μm; based on the total mass of active material A, active material B and active material C, the mass percentage of active material A is 20.0%.

[0123] Embodiment 6:

[0124] The steps of Example 6 are the same as those of Example 5, except that, during the preparation of the positive electrode sheet, the weight ratio of active material A to active material B is adjusted from 60:40 to 75:25; based on the total mass of active material A, active material B and active material C, the mass percentage of active material A is 30.0%.

[0125] Embodiment 7:

[0126] Embodiment 7 is divided into the following steps:

[0127] 1. Preparation of positive electrode sheet:

[0128] (1) Weigh the materials according to the following weight ratio: (active material: binder: conductive agent = 97.0:1.5:1.5), wherein the active material consists of active material A and active material B, active material A is selected from carbon-coated lithium iron phosphate, active material B is selected from lithium cobalt oxide, and the weight ratio of active material A to active material B is 1:2. Put the above materials into a planetary vacuum disperser and dry mix them for 30 minutes; then add an organic solvent NMP with a weight of 30% of the total weight of the above materials, stir for 1 hour, and then add an appropriate amount of NMP and disperse at high speed for 3 hours to prepare a qualified slurry with a viscosity falling within the range of 4000 mPa·s-9000 mPa·s.

[0129] (2) The qualified positive electrode slurry is coated onto an aluminum foil current collector with a single-side coating thickness of 30 μm, and then dried in an oven to obtain a pole piece including a first material layer.

[0130] (3) Weigh the materials according to the following weight ratio: (active material C: binder: conductive agent = 97.0:1.5:1.5), wherein the active material C is selected from lithium cobalt oxide, and place the above materials in a planetary vacuum disperser for dry mixing for 30 minutes; then add an organic solvent NMP whose weight is 30% of the total weight of the above materials, stir for 1 hour, add an appropriate amount of NMP and disperse at high speed for 3 hours to prepare a qualified slurry with a viscosity falling within the range of 4000mPa·s-9000mPa·s.

[0131] (4) The positive electrode slurry obtained in (3) is coated on the electrode sheet prepared in (2) with a single-side coating thickness of 90 μm, and then dried in an oven to obtain a composite positive electrode sheet. In the obtained composite positive electrode sheet, the mass percentage of active material A is 8.3% based on the total mass of active material A, active material B and active material C.

[0132] 2. Preparation of negative electrode sheet:

[0133] Artificial graphite, conductive agent Super P, thickener sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) are fully stirred and mixed in an appropriate amount of deionized water solvent according to a weight ratio of 95.0:1.5:1.5:2 to form a uniform negative electrode slurry. The slurry is coated on the negative electrode current collector copper foil, dried and cold pressed to obtain a negative electrode active material layer, and then cut, slit, and welded to the pole ear to obtain the negative electrode.

[0134] 3. Preparation of lithium-ion batteries:

[0135] The prepared positive electrode, negative electrode and separator (composed of a 9 μm PE polyethylene film coated with a 2 μm boehmite ceramic coating on both sides) were stacked in order, so that the separator was placed between the positive electrode and the negative electrode to play an isolating role, and then wound to obtain a bare cell; the bare cell was placed in an outer packaging foil aluminum-plastic film, and the electrolyte (50% EMC + 30% EC + 20% DEC + 1.1M LiPF6 +

[0136] 1%LiPO 2 F 2 +1% VC (vinyl carbonate) +1% FEC) is injected into the dried bare battery cell, and the preparation of the lithium-ion battery is completed through processes such as vacuum packaging, standing, formation, shaping, and capacity testing.

[0137] Embodiment 8:

[0138] Embodiment 8 is divided into the following steps:

[0139] 1. Preparation of positive electrode sheet:

[0140] (1) Weigh the materials according to the following weight ratio: (active material: binder: conductive agent = 97.0:1.5:1.5), wherein the active material consists of active material A and active material B, active material A is selected from carbon-coated lithium manganese iron phosphate, active material B is selected from lithium manganate, and the weight ratio of active material A to active material B is 2:1. Put the above materials into a planetary vacuum disperser and dry mix them for 30 minutes; then add an organic solvent NMP with a weight of 30% of the total weight of the above materials, stir for 1 hour, and then add an appropriate amount of NMP and disperse at high speed for 3 hours to prepare a qualified slurry with a viscosity falling within the range of 4000 mPa·s-9000 mPa·s.

[0141] (2) The qualified positive electrode slurry is coated onto an aluminum foil current collector with a single-side coating thickness of 30 μm, and then dried in an oven to obtain a pole piece including a first material layer.

[0142] (3) Weigh the materials according to the following weight ratio: (active material C: binder: conductive agent = 97.0:1.5:1.5), wherein the active material C is selected from lithium nickel cobalt manganese oxide, and place the above materials in a planetary vacuum disperser for dry mixing for 30 minutes; then add an organic solvent NMP whose weight is 30% of the total weight of the above materials, stir for 1 hour, add an appropriate amount of NMP and disperse at high speed for 3 hours to prepare a qualified slurry with a viscosity falling within the range of 4000mPa·s-9000mPa·s.

[0143] (4) The positive electrode slurry obtained in (3) is coated on the electrode sheet obtained in (2) with a single-side coating thickness of 90 μm, and then dried in an oven to obtain a composite positive electrode sheet. In the obtained composite positive electrode sheet, the mass percentage of active material A is 16.6% based on the total mass of active material A, active material B and active material C.

[0144] 2. Preparation of negative electrode sheet:

[0145] Artificial graphite, conductive agent Super P, thickener sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) are fully stirred and mixed in an appropriate amount of deionized water solvent according to a weight ratio of 95.0:1.5:1.5:2 to form a uniform negative electrode slurry. The slurry is coated on the negative electrode current collector copper foil, dried and cold pressed to obtain a negative electrode active material layer, and then cut, slit, and welded to the pole ear to obtain the negative electrode.

[0146] 3. Preparation of lithium-ion batteries:

[0147] The prepared positive electrode, negative electrode and separator (composed of a 9 μm PE polyethylene film coated with a 2 μm boehmite ceramic coating on both sides) were stacked in order, so that the separator was placed between the positive electrode and the negative electrode to play an isolating role, and then wound to obtain a bare cell; the bare cell was placed in an outer packaging foil aluminum-plastic film, and the electrolyte (50% EMC + 30% EC + 20% DEC + 1.1M LiPF6 +

[0148] 1%LiPO 2 F 2 +1% VC (vinyl carbonate) +1% FEC) is injected into the dried bare battery cell, and the preparation of the lithium-ion battery is completed through processes such as vacuum packaging, standing, formation, shaping, and capacity testing.

[0149] Embodiment 9:

[0150] Embodiment 9 is divided into the following steps:

[0151] 1. Preparation of positive electrode sheet:

[0152] (1) Weigh the materials according to the following weight ratio: (active material: binder: conductive agent = 97.0:1.5:1.5), wherein the active material consists of active material A and active material B, active material A is selected from carbon-coated lithium iron phosphate, active material B is selected from nickel cobalt manganese oxide, and the weight ratio of active material A to active material B is 1:3. Put the above materials into a planetary vacuum disperser and dry mix them for 30 minutes; then add an organic solvent NMP with a weight of 30% of the total weight of the above materials, stir for 1 hour, and then add an appropriate amount of NMP and disperse at high speed for 3 hours to prepare a qualified slurry with a viscosity falling within the range of 4000 mPa·s-9000 mPa·s.

[0153] (2) The qualified positive electrode slurry is coated onto an aluminum foil current collector with a single-side coating thickness of 30 μm, and then dried in an oven to obtain a pole piece including a first material layer.

[0154] (3) Weigh the materials according to the following weight ratio: (active material C: binder: conductive agent = 97.0:1.5:1.5), wherein the active material C is selected from lithium nickel cobalt manganese oxide, and place the above materials in a planetary vacuum disperser for dry mixing for 30 minutes; then add an organic solvent NMP whose weight is 30% of the total weight of the above materials, stir for 1 hour, add an appropriate amount of NMP and disperse at high speed for 3 hours to prepare a qualified slurry with a viscosity falling within the range of 4000mPa·s-9000mPa·s.

[0155] (4) The positive electrode slurry obtained in (3) is coated on the electrode sheet obtained in (2) with a single-side coating thickness of 90 μm, and then dried in an oven to obtain a composite positive electrode sheet. In the obtained composite positive electrode sheet, the mass percentage of active material A is 6.25% based on the total mass of active material A, active material B and active material C.

[0156] 2. Preparation of negative electrode sheet:

[0157] Artificial graphite, conductive agent Super P, thickener sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) are fully stirred and mixed in an appropriate amount of deionized water solvent according to a weight ratio of 95.0:1.5:1.5:2 to form a uniform negative electrode slurry. The slurry is coated on the negative electrode current collector copper foil, dried and cold pressed to obtain a negative electrode active material layer, and then cut, slit, and welded to the pole ear to obtain the negative electrode.

[0158] 3. Preparation of lithium-ion batteries:

[0159] The prepared positive electrode, negative electrode and separator (composed of a 9 μm PE polyethylene film coated with a 2 μm boehmite ceramic coating on both sides) were stacked in order, so that the separator was placed between the positive electrode and the negative electrode to play an isolating role, and then wound to obtain a bare cell; the bare cell was placed in an outer packaging foil aluminum-plastic film, and the electrolyte (50% EMC + 30% EC + 20% DEC + 1.1M LiPF6 +

[0160] 1%LiPO 2 F 2 +1% VC (vinyl carbonate) +1% FEC) is injected into the dried bare battery cell, and the preparation of the lithium-ion battery is completed through processes such as vacuum packaging, standing, formation, shaping, and capacity testing.

[0161] Embodiment 10:

[0162] The steps of Example 10 are the same as those of Example 9, except that the average particle size of the active material A used in Example 10 is different, as shown in Table 1.

[0163] Embodiment 11:

[0164] The steps of Example 11 are the same as those of Example 9, except that the average particle size of the active material A used in Example 11 is different, as shown in Table 1.

[0165] Embodiment 12:

[0166] The steps of Example 12 are the same as those of Example 1, except that the average particle size of the active material B used in Example 12 is different, as shown in Table 1.

[0167] Embodiment 13:

[0168] The steps of Example 13 are the same as those of Example 1, except that the average particle size of the active material B used in Example 12 is different, as shown in Table 1.

[0169] Embodiment 14:

[0170] The steps of Example 14 are the same as those of Example 1, except that the average particle size of the active material B used in Example 14 is different, as shown in Table 1.

[0171] Embodiment 15:

[0172] The steps of Example 15 are the same as those of Example 1, except that the average particle size of the active material C used in Example 15 is different, as shown in Table 1.

[0173] Embodiment 16:

[0174] The steps of Example 16 are the same as those of Example 1, except that the average particle size of the active material C used in Example 16 is different, as shown in Table 1.

[0175] Embodiment 17:

[0176] The steps of Example 17 are the same as those of Example 1, except that the average particle size of the active material C used in Example 17 is different, as shown in Table 1.

[0177] Comparative Example 1:

[0178] Comparative Example 1 comprises the following steps:

[0179] 1. Preparation of positive electrode sheet:

[0180] (1) Materials are weighed in the following weight ratio: (active material: binder: conductive agent = 97.0:1.5:1.5), wherein the active material is selected from lithium nickel cobalt manganese oxide, and the above materials are placed in a planetary vacuum disperser for dry mixing for 30 minutes; then, an organic solvent NMP whose weight is 30% of the total weight of the above materials is added, and after stirring for 1 hour, an appropriate amount of NMP is added, and high-speed dispersion is performed for 3 hours to prepare a qualified slurry with a viscosity falling within the range of 4000 mPa·s-9000 mPa·s.

[0181] (2) The positive electrode slurry obtained in (1) is coated on the positive electrode current collector with a single-side coating thickness of 135 μm, and then dried in an oven to obtain a composite positive electrode sheet.

[0182] 2. Preparation of negative electrode sheet:

[0183] Artificial graphite, conductive agent Super P, thickener sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) are fully stirred and mixed in a proper amount of deionized water solvent according to a weight ratio of 95:1.5:1.5:2 to form a uniform negative electrode slurry. The slurry is coated on the negative electrode current collector copper foil, dried and cold pressed to obtain a negative electrode active material layer, and then cut, slit, and weld the pole ears to obtain a negative electrode.

[0184] 3. Preparation of lithium-ion batteries:

[0185] The prepared positive electrode, negative electrode and separator (composed of a 9 μm PE polyethylene film coated with a 2 μm boehmite ceramic coating on both sides) were stacked in order, so that the separator was placed between the positive electrode and the negative electrode to play an isolating role, and then wound to obtain a bare cell; the bare cell was placed in an outer packaging foil aluminum-plastic film, and the electrolyte (50% EMC + 30% EC + 20% DEC + 1.1M LiPF6 +

[0186] 1%LiPO 2 F 2 +1% VC (vinyl carbonate) +1% FEC) is injected into the dried bare battery cell, and the preparation of the lithium-ion battery is completed through processes such as vacuum packaging, standing, formation, shaping, and capacity testing.

[0187] Comparative Example 2:

[0188] The steps of Comparative Example 2 are the same as those of Example 2, except that the active material in the first material layer of Comparative Example 1 is entirely composed of active material A (lithium iron phosphate). In the composite positive electrode sheet obtained in Comparative Example 2, the mass percentage of active material A is about 10.0% based on the total mass of active material A and active material C.

[0189] Comparative Example 3:

[0190] Comparative Example 3 following steps:

[0191] 1. Preparation of positive electrode sheet:

[0192] (1) Weigh materials according to the following weight ratio: (active material A: binder: conductive agent = 97.0:1.5:1.5), wherein active material A is lithium nickel cobalt manganese oxide, and place the above materials in a planetary vacuum disperser for dry mixing for 30 minutes; then add an organic solvent NMP whose weight is 30% of the total weight of the above materials, stir for 1 hour, then add an appropriate amount of NMP, and disperse at high speed for 3 hours to prepare a qualified slurry with a viscosity falling within the range of 4000 mPa·s-9000 mPa·s.

[0193] (2) The qualified positive electrode slurry is coated onto an aluminum foil current collector with a single-side coating thickness of 90 μm, and then dried in an oven to obtain a pole piece including a first material layer.

[0194] (3) Weigh the materials according to the following weight ratio: (active material C: binder: conductive agent = 97.0:1.5:1.5), wherein the active material C is a mixture of lithium iron phosphate and lithium nickel cobalt manganese oxide (the mass ratio of lithium iron phosphate to lithium nickel cobalt manganese oxide is 1:3), put the above materials into a planetary vacuum disperser and dry mix them for 30 minutes; then add an organic solvent NMP whose weight is 30% of the total mass of the above materials, stir for 1 hour, add an appropriate amount of NMP and disperse at high speed for 3 hours to prepare a qualified slurry with a viscosity falling within the range of 4000mPa·s-9000mPa·s.

[0195] (4) The positive electrode slurry obtained in (3) is coated on the electrode sheet prepared in (2) with a single-side coating thickness of 30 μm, and then dried in an oven to obtain a composite positive electrode sheet. In the obtained composite positive electrode sheet, the mass percentage of active material A is about 6.2% based on the total mass of active material A, active material B and active material C.

[0196] 2. Preparation of negative electrode sheet:

[0197] Artificial graphite, conductive agent Super P, thickener sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) are fully stirred and mixed in an appropriate amount of deionized water solvent according to a weight ratio of 95.0:1.5:1.5:2 to form a uniform negative electrode slurry. The slurry is coated on the negative electrode current collector copper foil, dried and cold pressed to obtain a negative electrode active material layer, and then cut, slit, and welded to the pole ear to obtain the negative electrode.

[0198] 3. Preparation of lithium-ion batteries:

[0199] The prepared positive electrode, negative electrode and separator (composed of a 9 μm PE polyethylene film coated with a 2 μm boehmite ceramic coating on both sides) were stacked in order, so that the separator was placed between the positive electrode and the negative electrode to play an isolating role, and then wound to obtain a bare cell; the bare cell was placed in an outer packaging foil aluminum-plastic film, and the electrolyte (50% EMC + 30% EC + 20% DEC + 1.1M LiPF6 + 1% LiPO 2 F 2 +1% VC (vinyl carbonate) +1% FEC) is injected into the dried bare battery cell, and the preparation of the lithium-ion battery is completed through processes such as vacuum packaging, standing, formation, shaping, and capacity testing.

[0200] Comparative Example 4:

[0201] The steps of Comparative Example 4 are the same as those of Example 1, except that the average particle sizes of active materials B and C used in Comparative Example 4 are different, as shown in Table 1.

[0202] The compositions of the positive electrode materials used in Examples 1-17 and Comparative Examples 1-4 are shown in Table 1:

[0203] [Table 1]

[0204]

[0205]

[0206] Electrochemical testing:

[0207] When Example 1 and Comparative Example 1 are discharged at 20% SOC at the end of discharge, the voltage of the battery is discharged at 0.6C to 5% SOC. The curves of the voltage change with time are as follows: Figure 1 shown.

[0208] Then, discharge tests were performed on Examples 1-17 and Comparative Examples 1-4, and their impedance, cycle life and capacity retention were measured, respectively. The specific values ​​are shown in Table 2:

[0209] [Table 2]

[0210] Example DCR(mΩ) -20℃ capacity retention rate (%) Cycle life (cycles) 3C / 1C rate discharge Example 1 1.8 88.7 1630 92.9 Example 2 2.0 89.2 1480 92.4 Example 3 2.1 88.4 1880 91.7 Example 4 1.7 88.2 1820 91.9 Example 5 1.9 87.6 1750 91.4 Example 6 2.4 85.7 1540 90.8 Example 7 1.4 88.6 1320 94.5 Example 8 3.8 87.9 1260 91.9 Example 9 1.7 89.3 1560 93.1 Example 10 1.8 88.9 1590 92.8 Embodiment 11 1.9 88.4 1620 92.3 Example 12 1.8 88.5 1600 92.4 Example 13 2.1 88.3 1550 92.1 Embodiment 14 2.3 87.8 1510 91.1 Embodiment 15 1.8 87.4 1480 91.7 Example 16 2.5 86.6 1430 90.8 Embodiment 17 3.3 85.2 1290 89.6 Comparative Example 1 2.7 82.4 1090 89.2 Comparative Example 2 3.5 75.2 820 88.5 Comparative Example 3 4.8 68.3 850 83.4 Comparative Example 4 4.5 70.3 920 85.7

[0211] from Figure 1 It can be seen that compared with Comparative Example 1 in which only nickel cobalt manganese oxide is used as the active material, the presence of lithium iron phosphate in the positive electrode plate prepared in Example 1 relaxes the voltage curve and makes the discharge power more stable at low SOC, so the voltage consistency of each battery cell in the battery pack is better, thereby improving the overall life of the battery pack. In Comparative Example 1, only nickel cobalt manganese oxide ternary material is used, and its terminal polarization is large (the discharge cut-off voltage is reached before 5% SOC), which aggravates the voltage difference at the ends of different batteries in the battery pack. Due to the over-discharge behavior of individual batteries, the life of the entire battery pack is deteriorated, which not only increases the management difficulty of the battery management system, but also reduces the range of available discharge depth.

[0212] It can be seen from Table 2 that since the first material layer in Comparative Example 2 only uses lithium iron phosphate and the second material layer uses lithium nickel cobalt manganese oxide, lithium iron phosphate has only a one-dimensional lithium ion channel when deintercalating lithium, and lithium nickel cobalt manganese oxide has a two-dimensional channel when deintercalating lithium, and their diffusion coefficients are inconsistent, resulting in a large interface impedance and reducing the rate performance; and during the cycle process, the upper and lower layers expand differently, and the accumulation of stress may cause the contact between the two active layers to further deteriorate, thereby affecting the long-term cycle life; Example 1-2 also introduces lithium nickel cobalt manganese oxide ternary material in the first material layer, so that the diffusion coefficients of the upper and lower layers are close, thereby improving the rate performance and increasing the cycle life; in addition, it can be seen from Table 2 that the greater the difference in particle size, the greater the contact between the particles, the greater the internal resistance, and the lower the electrochemical performance.

[0213] Lithium intercalation and deintercalation occurs at the interface between the active material and the electrolyte. Lithium iron phosphate or lithium iron manganese phosphate has only one-dimensional lithium ion channels. If it is distributed in the second active layer, a large amount of lithium iron phosphate or lithium iron manganese phosphate is close to the surface. During high-rate charge and discharge, the lithium at the interface cannot be intercalated and deintercalated in time, causing the active lithium to fail and deteriorate in performance. And because the carbon coating on the surface of lithium iron phosphate in the first active layer provides more electron channels in the area close to the pole piece, it reduces the overall impedance and improves the performance at low temperatures.

[0214] The reason why the upper limit of the weight percentage of active material A is set to 30.0% is mainly because active material A is a phosphate material with relatively low capacity. If too much is added, the capacity and energy density will be reduced.

[0215] Although illustrative embodiments have been shown and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present disclosure, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present disclosure.

Claims

1. A positive electrode sheet, characterized in that: The positive electrode sheet includes a positive electrode current collector, a first material layer disposed on at least one surface of the positive electrode current collector, and a second material layer disposed on a surface of the first material layer away from the positive electrode current collector; the first material layer includes active material A and active material B; the second material layer includes active material C; wherein: The active material A is selected from lithium iron phosphate and / or lithium iron manganese phosphate; The active material B is selected from one or more of lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium manganese oxide and lithium nickel manganese oxide; The active material C is selected from one or more of lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium manganese oxide and lithium nickel manganese oxide.

2. The positive electrode sheet according to claim 1, wherein: The first material layer has a thickness of 15-40 μm.

3. The positive electrode sheet according to claim 1, wherein: The second material layer has a thickness of 60-135 μm.

4. The positive electrode sheet according to claim 1, wherein: In the first material layer, a mass ratio of the active material A to the active material B is 1:3 to 3:

1.

5. The positive electrode sheet according to claim 1, wherein: Based on the total weight of the active material A, the active material B and the active material C, the weight percentage of the active material A is 2.5% to 30.0%.

6. The positive electrode sheet according to claim 5, wherein: Based on the total weight of the active material A, the active material B and the active material C, the weight percentage of the active material A is 2.5% to 6.2%.

7. The positive electrode sheet according to claim 1, wherein: The ratio of the average particle sizes of the active material B to the active material A is selected from 3:1 to 13:

1.

8. The positive electrode sheet according to claim 1, wherein: The ratio of the average particle sizes of the active material C and the active material A is selected from 3:1 to 13:

1.

9. A method for preparing the positive electrode sheet according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: Step 1: Active material A, active material B, a binder and a conductive agent are stirred evenly by dry mixing, and then N-methylpyrrolidone is added and stirred evenly to obtain a first positive electrode slurry; Step 2: coating the first positive electrode slurry onto at least one surface of the positive electrode current collector, wherein the single-side coating thickness is 15-40 μm, and drying to obtain a pole piece including the first material layer; Step 3: stir the active material C, the binder and the conductive agent evenly by dry mixing, and then add N-methylpyrrolidone and stir evenly to obtain a second positive electrode slurry; Step 4: coating the second positive electrode slurry onto the surface of the electrode sheet obtained in step 2 away from the positive electrode current collector, wherein the single-side coating thickness is 60-135 μm, and drying to obtain the positive electrode sheet.

10. The method according to claim 9, wherein: The solid content of the first positive electrode slurry and the second positive electrode slurry is 45% to 78%, and the viscosity is 3000 mPa·s to 15000 mPa·s.

11. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet according to any one of items 1-8, and the lithium-ion battery further comprises a negative electrode sheet and an electrolyte. 12 . An electrical device comprising the lithium-ion battery according to claim 11 .

Citation Information

Cited By

  • Positive plate, battery comprising positive plate and electric device

    CN120300128A

  • Positive pole piece, preparation method thereof and lithium ion battery

    CN120432495A

  • Positive pole piece, lithium ion battery comprising positive pole piece, and electronic device comprising positive pole piece

    CN122067976A

  • A positive electrode sheet, and a lithium ion battery and an electronic device comprising the same

    CN122067976B